2000
DOI: 10.1111/j.8755-8920.2000.440404.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Factor Activity in Serum of Patients with Surgical Abortion

Abstract: Quantitative study of EPF activity along temporal dimensions (duration) due to surgical abortion further promotes the efficiency to take EPF activity and its rate of change as truly index for monitoring embryonic care and development of normal pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Th ese results are concordant with the previous study about detection of subclinical pregnancy loss using Cp10 in clomiphene citrate cycles (Shahani et al 1995). Cheng et al demonstrated sudden drop in Cp10 to the levels of negative controls in surgical abortion-applied patients aft er 5 -7 days (Cheng et al 2000). Th eir results support our fi ndings about decrease in Cp10 levels from day 2 to day 8 in non-pregnant group (Figure 1a).…”
Section: Discussionsupporting
confidence: 92%
“…Th ese results are concordant with the previous study about detection of subclinical pregnancy loss using Cp10 in clomiphene citrate cycles (Shahani et al 1995). Cheng et al demonstrated sudden drop in Cp10 to the levels of negative controls in surgical abortion-applied patients aft er 5 -7 days (Cheng et al 2000). Th eir results support our fi ndings about decrease in Cp10 levels from day 2 to day 8 in non-pregnant group (Figure 1a).…”
Section: Discussionsupporting
confidence: 92%
“…Second, EPF levels fall to normal within 2-5 days after induced abortion (Cheng et al 2000;Hübel et al 1989). This supports EPF's role as a marker for pregnancy as well as non-pregnancy.…”
Section: Early Pregnancy Factor and Lng-ecmentioning
confidence: 54%
“…The maternal immune system must tolerate an allogenic fetus. Early pregnancy factor (EPF) is one early indicator of immunosuppressive activity (Shahani et al 1994, Cheng et al 2000. EPF purifi ed from human platelets is identical to chaperonin 10 (cpn-10) or heat shock protein 10 (HSP-10) (Cavanagh and Morton 1994, Quinn et al 1994, Cavanagh 1996).…”
mentioning
confidence: 99%